WRF‐TEB: Implementation and Evaluation of the Coupled Weather Research and Forecasting (WRF) and Town Energy Balance (TEB) Model. (18th August 2020) - Meyer, D.; Schoetter, R.; Riechert, M.; Verrelle, A.; Tewari, M.; Dudhia, J.; Masson, V.; van Reeuwijk, M.; Grimmond, S.
Abstract: Urban land surface processes need to be represented to inform future urban climate and building energy projections. Here, the single layer urban canopy model Town Energy Balance (TEB) is coupled to the Weather Research and Forecasting (WRF) model to create WRF‐TEB. The coupling method is described generically, implemented into software, and the code and data are released with a Singularity image to address issues of scientific reproducibility. The coupling is implemented modularly and verified by an integration test. Results show no detectable errors in the coupling. Separately, a meteorological evaluation is undertaken using observations from Toulouse, France. The latter evaluation, during an urban canopy layer heat island episode, shows reasonable ability to estimate turbulent heat flux densities and other meteorological quantities. We conclude that new model couplings should make use of integration tests as meteorological evaluations by themselves are insufficient, given that errors are difficult to attribute because of the interplay between observational errors and multiple parameterization schemes (e.g., radiation, microphysics, and boundary layer). Plain Language Summary: With increasing urbanization and climate change, estimates of possible future urban climate and building energy scenarios are needed. Weather models (e.g., Weather Research and Forecasting; WRF) provide the state of the atmosphere, and urban land surface models (e.g., Town Energy Balance; TEB) allow the interactions and feedbacks of people—buildings—atmosphere to be investigated. WRF‐TEB is a free and open‐source model aimed at the urban climate and energy community to investigate applications such as the energy consumption associated with air conditioners, or the generation of solar energy in cities. Key Points: WRF‐TEB accounts for urban canopy energy exchanges, building energy demand, and neighborhood vegetation Coupled weather model development and scientific reproducibility are demonstrated The coupling is verified through an integration test and evaluated with meteorological observations